Teaching English Through Social Media: Teachers’ Perceptions - Murni Mahmud; Abdul Halim; Fatimah Hidayahni (Seminar Nasional LP2M UNM, 2021)
Abstract. The use of social media in human’s life is undeniable, including in teaching. Nowadays, some of the social media applications which are commonly used for social relations are now be applied in teaching language skills, especially in teaching English. For this purpose, this study aims to explore the use of social media in teaching English based on the teachers and students’ perceptions. This research applied a qualitative research design taking 50 teachers of English in the universities in Makassar. The data of this research were collected by employing a survey of Google Form and analyzed descriptively and qualitatively. The result of the research shows that the English teachers in the universities in Makassar gave their positive perceptions about the use of social media in teaching English. Some of the answers of the informants gave some strategies to be used to take the advantage from the use of social media. It can be seen that some of the social media application such as Instagram and Facebook can be applied in teaching English skills. Findings from this study are worthy of reading for English language teaching practitioners in their effort to create interactive teaching and learning activities in the class.Keyword: Social media, Facebook, Instagram, Online Learning, English Language Teaching